2011
DOI: 10.1002/hbm.21191
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of electrical stimulation and voluntary hand movement in SII and the cerebellum during simulated therapeutic functional electrical stimulation in healthy adults

Abstract: The therapeutic application of functional electrical stimulation (FES) has shown promising clinical results in the rehabilitation of post-stroke hemiplegia. It appears that the effect is optimal when the patterned electrical stimulation is used in close synchrony with voluntary movement, although the neural mechanisms that underlie the clinical successes reported with therapeutic FES are unknown. One possibility is that therapeutic FES takes advantage of the sensory consequences of an internal model. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 58 publications
11
56
0
Order By: Relevance
“…Moreover, the changes in the applied muscle gradually increased in the later temporal phases and hence we hypothesized that for the agonist muscle, the combination method may cause a summation effect along with the stimulation time in the motor cortex. The finding on the effect in the agonist muscle was consistent with the results of functional MRI studies [19,20], indicating that peripheral electrical stimulation modulates activity not only in M1 but also in multiple brain areas, particularly the somatosensory cortex and the cerebellum [21]. Both the afferent input and temporal summation may activate the neural activity in the motor cortex of the agonist muscle.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the changes in the applied muscle gradually increased in the later temporal phases and hence we hypothesized that for the agonist muscle, the combination method may cause a summation effect along with the stimulation time in the motor cortex. The finding on the effect in the agonist muscle was consistent with the results of functional MRI studies [19,20], indicating that peripheral electrical stimulation modulates activity not only in M1 but also in multiple brain areas, particularly the somatosensory cortex and the cerebellum [21]. Both the afferent input and temporal summation may activate the neural activity in the motor cortex of the agonist muscle.…”
Section: Discussionsupporting
confidence: 86%
“…The afferent input because of the electrical stimulation of the periphery can influence the excitability of the corresponding motor area [1,4,16]. A study conducted by Iftime-Nielsen et al [21] indicated that specific changes in the secondary somatosensory area activity in response to combined VC and NMES may reflect a better match between the internal model [22] and the actual sensory feedback. This combination of NMES and VC had a significant effect on MMG-MEP size in the agonist muscle.…”
Section: Discussionmentioning
confidence: 99%
“…When sensory feedback was intact (i.e. BASE and INFL) we tested the differences between VOL, FES‐as and FES‐ev in order to confirm the previously reported bilateral S2 activation during the FES‐ev and FES‐as conditions compared with VOL (Iftime‐Nielsen et al ., ). These tests were performed using t ‐contrasts in order to reveal the directional changes in the BOLD fMRI signal between the different tasks, i.e.…”
Section: Resultsmentioning
confidence: 97%
“…Iftime-Nielsen et al [36] reported that neuromuscular stimulation combined with voluntary activation produces more activation of the cerebellum and less activation of secondary somatosensory cortex than dose neuromuscular stimulation alone in normal subjects. Neuroimaging studies of FES-evoked (FES delivered in the absence of voluntary activation) and FES-assisted (FES delivered to augment voluntary activation) movements have suggested bilateral secondary somatosensory cortex (S2) activation is related to the application of therapeutic FES [36].…”
Section: Mechanism Of Fes Effectsmentioning
confidence: 99%
“…Neuroimaging studies of FES-evoked (FES delivered in the absence of voluntary activation) and FES-assisted (FES delivered to augment voluntary activation) movements have suggested bilateral secondary somatosensory cortex (S2) activation is related to the application of therapeutic FES [36]. Another study suggested FES-related S2 activation is mainly a sensory phenomenon and does not reflect integration of sensory signals with motor commands [37].…”
Section: Mechanism Of Fes Effectsmentioning
confidence: 99%